Thinking through quality questioning : deepening student engagement - Walsh, Jackie A.; Sattes, Beth D. (Beth Dankert) (Thousand Oaks, Calif. : Corwin Press, 2011)
'This groundbreaking book provides teachers with an accessible, research-based blueprint for developing student meta-cognitive skills and ensuring that students take responsibility for their own learning. The authors use the findings of cognitive scientists to highlight quality questioning behaviors and explain how to apply them for improved student outcomes'-- Provided by publisher.
'Thinking Though Quality Questioning provides teachers with an accessible, research-based blueprint for developing student meta-cognitive skills and ensuring that students take responsibility for their own learning. In this groundbreaking book, Walsh and Sattes use the findings of cognitive scientists to highlight quality questioning behaviors and explain how to connect these to discrete student meta-cognitive outcomes. Each chapter explicates teacher best practice in questioning and relates this to how students think and how they can be trained to manage their own learning'-- Provided by publisher.
Machine generated contents note: PrefaceAcknowledgementsAbout the Authors1. Framework for Thinking through Quality Questioning-In what ways can quality questioning advance both student and teacher thinking?2. Frame Quality Questions-What are the characteristics of questions that engage students in thinking and deep learning about content?3. Strengthen Thinking to Learn Behaviors -How can teachers and students use quality questioning to deepen thinking and increase learning?4. Use Formative Feedback-How can questioning serve as formative assessment and feedback to advance student learning?5. Developing Response-Ability-In what ways can teachers cultivate and nourish student responsibility for learning?6. Create a Culture for Thinking: How can you use quality questioning to create a classroom culture where students and teacher work together to advance thinking and knowing?Resource A: Processes to Engage Learners in ThinkingResource B: Sample Tools for Formative AssessmentReferencesIndex.
Includes bibliographical references and index.
Keywords: Inquiry-based learning; Active learning; Thought and thinking -- Study and teaching